Determination of arsenic (III) and arsenic (V) species by preconcentration and inductively coupled plasma mass spectrometry (ICP-MS) in drinking water samples analysis. - Rahman, Md. Mokhlesur; Yusof, Alias Mohd; Wood, Abdul Khalik; A., Shamsiah (Trans Tech Publications, Switzerland, 2011)
A simple and less expensive solvent extraction method was used with inductively coupled plasma mass spectrometry (ICP-MS) in the speciation of two environmentally significant,toxic forms of arsenic: arsenite and arsenate. Dissolved inorganic arsenic species in drinking waters from reservoirs and treatment plants were determined by the inductively coupled plasma mass spectrometry analyses. Prior to the analysis the water samples were precocentrated by solvent extraction using APCDT to separate the arsenic species from elemental interferences. The detection limit of this method achieved was 0.059 μgL-1. The suitability of the technique in this work is discussed in relation to risk assessment studies of public health.